Formulation Design and Characterization of Colon-targeted Mesalamine Microspheres and their Biodistribution Potential Study in Mice - Kar, N. R. (Asian Journal of Pharmaceutics (AJP), 2019)
Aim: The aim of this study is to design formulations of mesalamine microspheres (MMS) for the treatment of Crohn’s disease and ulcerative colitis in the colon. Materials and Methods: Emulsification solvent diffusion method was employed for the preparation of MMS coated with Eudragit RS/ES-100 to prevent the drug release in the stomach. The prepared microspheres were characterized for surface morphology, drug entrapment efficiency, drug loading, and in vitro drug release study. Results and discussion: The micromeritic studies showed that the prepared microspheres had improved flowability. The result obtained was found in the desired ranges, where percentage yield ranging from 65.75% to 67.46%, drug entrapment efficiency from 83.02% to 86.42%, and mean particle size ranges from 6.99 μm to 15.37 μm. Scanning electron microscopy permitted a surface topographical analysis. From the biodistribution study, it can be observed that AUC0–t of the microspheres was 2.63-folds greater than the solution (P < 0.05) in the colon. Conclusion: The study reveals that drug release was significant at pH 7.4 from the microspheres at colon region, so the drug will be better absorbed in colon and can be used for successful treatment of the Crohn’s disease and ulcerative colitis